Insulin-like growth factor 1 receptor signaling regulates embryonic epicardial cell proliferation through focal adhesion kinase pathway. (31st August 2018) - Yan, Yuling; Qin, Qin; Wu, Ling; Jing, Xiaodong; Deng, Songbai; She, Qiang
Abstract: Embryonic epicardial cells (EPCs) can facilitate cardiomyocyte growth through secreting several essential growth factors, and participate in cardiac development through auto-differentiating into many cardiac cell lineages. Proper proliferation of EPCs is the precondition of these functions, so it is quite necessary to explore the mechanisms involving in EPC proliferation. In this study, we aimed to explore whether insulin-like growth factor 1 receptor (IGF1R) signaling participated in regulating the proliferation of EPCs. Our results showed that the expressions of IGF1R and its ligands IGF1 and IGF2 can be clearly spotted on the epicardium layer from E11.5d to E17.5d. Inhibition of IGF1R signaling using picropodophyllin or NVP-AEW541 significantly decreased the proliferation activity and blocked the cell cycle progression of epicardial cells in vitro . On the contrary, activating IGF1R with recombinant IGF1 and IGF2 promoted epicardial cell proliferation and cell cycle. We also found that decreased expression and phosphorylation of FAK in IGF1R inhibitor-treated cells and use of FAK inhibitor Y15 could significantly inhibit the IGFs-induced EPC proliferation. In conclusion, our results suggest that IGF1R signaling plays an important role in regulating EPC proliferation, and this effect may be mediated by FAK pathway.